Teman Sebaya dan Prospek Karier Terhadap Pemilihan Mata Kuliah Konsentrasi Terhadap Pemilihan Mata Kuliah Konsentrasi Pada Mahasiswa Pendidikan Ekonomi Angkatan 2023 Universitas Jambi - Rico Mario Siahaan; Muhammad Arif Liputo; Destri Yaldi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the importance of selecting concentration courses as one of the academic decisions students make. In this process, there are various factors believed to influence students’ decisions, including peers and career prospects. This study aims to determine the influence of peers and career prospects on the selection of concentration courses among students in the Economics Education Study Program, Class of 2023, at the University of Jambi, both partially and simultaneously. This study uses the Theory of Planned Behavior (TPB) as its theoretical framework. The study employs a quantitative approach using the causal-associative method. The research sample consisted of 90 students selected using simple random sampling. Data collection was conducted via a questionnaire that had been tested for validity and reliability, and the data were analyzed using multiple linear regression. The results of the study indicate that, partially, peers have a positive and significant effect on the selection of concentration courses, with a t-value> t-table (4.009 > 1.987), whereas career prospects do not have asignificant effect, with a t-calculated value < t-table (0.047 < 1.987). Simultaneously,peers and careerprospects have a positive and significant effecton the selection of concentration courses, with an F-calculated value > F-table(8.656 > 3.10) and contributing 16.6%. The results of this studyare expected to provide input for the Economics Education Study Program in improving information services and guidance for students inselecting concentration courses. mata kuliah konsentrasi.